PRAGMATISME SEBAGAI PARADIGMA PEMBELAJARAN: RESPONS PENDIDIKAN AGAMA KRISTEN TERHADAP PENDEKATAN LEARNING BY-DOING - Ridwan Rudiyanto Kajah Kore; Nanda Pinkan Ade Ningsi Ga Kale; Cindy Tamelab; Agnesia Selan; Sance Yunita Kause; Ireni Irnawati Pellokila (CV. Lafadz Jaya, 2025)
Pragmatism as a philosophy of education emphasizes direct experience, practical action, and problem-solving as the core of the learning process. This paradigm finds its relevance in the learning by doing approach, which positions learners as active participants in education. This article aims to examine pragmatism as a learning paradigm and to analyze the response of Christian Religious Education to the learning by doing approach within the context of formal education. This study employs a literature review method by analyzing educational philosophy literature, pragmatist theories, as well as theological and pedagogical sources related to Christian Religious Education. The findings indicate that the learning by doing approach aligns with pragmatic principles by emphasizing active learner engagement, experiential reflection, and the application of values in real-life contexts. From the perspective of Christian Religious Education, this paradigm is relevant to the formation of a living and contextual faith, where learners not only understand Christian teachings cognitively but also embody them through concrete actions. Therefore, pragmatism can serve as a constructive learning paradigm for Christian Religious Education, provided that it remains grounded in Christian theological values and oriented toward holistic Christian character formation.